2022
DOI: 10.3390/cancers14205072
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Hematological Malignancies

Abstract: Autophagy is a highly conserved metabolic pathway via which unwanted intracellular materials, such as unfolded proteins or damaged organelles, are digested. It is activated in response to conditions of oxidative stress or starvation, and is essential for the maintenance of cellular homeostasis and other vital functions, such as differentiation, cell death, and the cell cycle. Therefore, autophagy plays an important role in the initiation and progression of tumors, including hematological malignancies, where da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 240 publications
0
7
0
Order By: Relevance
“…Autophagy, activated in response to several conditions including oxidative stress and mitochondrial alteration, is an essential pathway aimed at eliminating unwanted intracellular elements, such as unfolded oxidized proteins or damaged organelles, to promote cell survival ( García Ruiz et al, 2022 ). To assess the induction of autophagy by OLDA treatment, we first analyzed the ATG12–ATG5 complex essential for autophagosome formation ( Kharaziha and Panaretakis, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy, activated in response to several conditions including oxidative stress and mitochondrial alteration, is an essential pathway aimed at eliminating unwanted intracellular elements, such as unfolded oxidized proteins or damaged organelles, to promote cell survival ( García Ruiz et al, 2022 ). To assess the induction of autophagy by OLDA treatment, we first analyzed the ATG12–ATG5 complex essential for autophagosome formation ( Kharaziha and Panaretakis, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The autophagy machinery is activated during cellular stresses to digest damaged organelles, unwanted proteins, and intracellular materials. Thus, given that it is indispensable to maintain cellular homeostasis, several reports highlight its anti-tumoral action in CML by controlling ROS and DNA damage ( Baquero et al, 2019 ; García Ruiz et al, 2022 ). It has been demonstrated that CD34 + leukemia stem cells display a high level of autophagic flux, and, more importantly, TKI treatment, as the flip side, stimulates autophagy responsible for leukemia stem cell survival and establishment of drug resistance ( Bellodi et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid deprivation has been shown to induce the activation of autophagy, which is considered a self-protective mechanism in tumour cells ( 55 57 ). Hermanova et al.…”
Section: Mechanism Of Drug Resistancementioning
confidence: 99%
“…Autophagy plays an important role in several CSC functions, including maintenance and survival [ 68 , 69 , 70 , 71 , 72 , 73 ], adaptation to the TME [ 74 , 75 , 76 ], migration and invasion [ 77 , 78 ], chemo- and immune-resistance [ 79 , 80 , 81 , 82 ], and metabolic reprogramming [ 83 , 84 , 85 ]. Numerous studies suggest that the inflammatory response in the TME is regulated by autophagy via TAMs and CAFs.…”
Section: Autophagy and Carcinogenesismentioning
confidence: 99%